1999
DOI: 10.2519/jospt.1999.29.9.526
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measurements of Walking and Running in People With Transtibial Amputations With 3 Different Prostheses

Abstract: Study Design: A 3-factor (foot type, speed, and mode of ambulation) repeated-measures experimental design was used. Objectives: To compare the differences in energy expenditure, gait efficiency, and relative exercise intensity in persons with transtibial amputations with various prostheses. Background: There is a need for improved prosthetic designs to accommodate physically active persons with lower-extremity amputations. Methods and Measures:We used progressive speeds of treadmill walking (53.64, 67.05, 80.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 13 publications
4
80
1
1
Order By: Relevance
“…However, this reduction is very small, with the mean cost of amputee walking across all ESR feet being 97.3 percent of that with a SACH foot. This confirms what only a few studies have shown with statistical significance (p < 0.05) [12][13]. The majority of studies have failed to obtain statistically significant results [3][4]6,[14][15][16][17][18], probably because of insufficient statistical power to detect such small differences.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, this reduction is very small, with the mean cost of amputee walking across all ESR feet being 97.3 percent of that with a SACH foot. This confirms what only a few studies have shown with statistical significance (p < 0.05) [12][13]. The majority of studies have failed to obtain statistically significant results [3][4]6,[14][15][16][17][18], probably because of insufficient statistical power to detect such small differences.…”
Section: Discussionsupporting
confidence: 78%
“…We required the studies to contain metabolic cost of walking data, either per minute or per meter. After the application of the four additional criteria, we identified nine articles [3,4,[12][13][14][15][16][17][18]] from Hofstad et al's [19] systematic review that contained the necessary data for our meta-analysis. In addition, we identified only one article (Mengelkoch et al [6]) published after the systematic review that contained the relevant data and met the necessary selection criteria for the normalization method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results would possibly differ when prosthetic systems are used that also incorporate flexible shank regions, such as those found in the Flex-Foot (Össur; Reykjavik, Iceland). However, as mentioned earlier, several studies have still found no difference in energy expenditure when the Flex-Foot is used compared with the SACH foot [4][5][6].…”
Section: Discussionmentioning
confidence: 89%
“…Energy cost and expenditure also correlate with level of amputation [2] and residual limb length [3] and have more recently been used in attempts to quantify differences between prosthetic feet within a population of prosthesis users. Three previous investigations on unilateral transtibial prosthesis users reported reduced energy expenditure with the use of energy storage and return (ESAR) prostheses compared with the solid-ankle cushioned heel (SACH) foot [4][5][6]. Seven other reports found no difference in energy expenditure with the use of the SACH and ESAR feet in persons with unilateral transtibial amputation [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%